2022
DOI: 10.3390/cells12010058
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Hyperhomocysteinemia Produces Memory Deficits Associated with Impairment of Long-Term Synaptic Plasticity in Young Rats

Abstract: Maternal hyperhomocysteinemia (HCY) is a common pregnancy complication caused by high levels of the homocysteine in maternal and fetal blood, which leads to the alterations of the cognitive functions, including learning and memory. In the present study, we investigated the mechanisms of these alterations in a rat model of maternal HCY. The behavioral tests confirmed the memory impairments in young and adult rats following the prenatal HCY exposure. Field potential recordings in hippocampal slices demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Synaptic plasticity, the ability of synapses to strengthen or weaken over time in response to changes in their activity, is fundamental to learning and memory processes. High methionine intake and hyperhomocysteinemia have been shown to impact synaptic plasticity by disrupting key molecular signaling pathways involved in synaptic function [223,[350][351][352][353][354]. Preclinical studies have demonstrated that a methionine-rich diet can impair long-term potentiation (LTP), a cellular mechanism underlying synaptic plasticity, leading to deficits in learning and memory [351,354,355].…”
Section: Methionine-rich Diet and Synaptic Function/neuronal Health 4...mentioning
confidence: 99%
See 1 more Smart Citation
“…Synaptic plasticity, the ability of synapses to strengthen or weaken over time in response to changes in their activity, is fundamental to learning and memory processes. High methionine intake and hyperhomocysteinemia have been shown to impact synaptic plasticity by disrupting key molecular signaling pathways involved in synaptic function [223,[350][351][352][353][354]. Preclinical studies have demonstrated that a methionine-rich diet can impair long-term potentiation (LTP), a cellular mechanism underlying synaptic plasticity, leading to deficits in learning and memory [351,354,355].…”
Section: Methionine-rich Diet and Synaptic Function/neuronal Health 4...mentioning
confidence: 99%
“…High methionine intake and hyperhomocysteinemia have been shown to impact synaptic plasticity by disrupting key molecular signaling pathways involved in synaptic function [223,[350][351][352][353][354]. Preclinical studies have demonstrated that a methionine-rich diet can impair long-term potentiation (LTP), a cellular mechanism underlying synaptic plasticity, leading to deficits in learning and memory [351,354,355]. Elevated homocysteine levels, stemming from high methionine intake, have been linked to reduced levels of brain-derived neurotrophic factor (BDNF) [356], a molecule essential for synaptic plasticity.…”
Section: Methionine-rich Diet and Synaptic Function/neuronal Health 4...mentioning
confidence: 99%